Polyclonal Mycobacterium avium infections in patients with AIDS: variations in antimicrobial susceptibilities of different strains of M. avium isolated from the same patient. - von Reyn, C F (1995)
Broth microdilution MICs were determined for pairs of strains isolated from five AIDS patients with polyclonal Mycobacterium avium infection. Four (80%) of the five patients were infected simultaneously with strains having different antimicrobial susceptibility patterns. These findings have implications for the interpretation of susceptibility data in M. avium prophylaxis and treatment trials.